Designing sea ice web APIs for ice information services - Liu, Xintao; Li, Songnian; Huang, Wei; Gong, Jun (Earth science informatics, 2015)
Due to climate change and global warming, sea ice studies have recently gained more and more attention from various fields. Despite previous work on sea ice data collection, digitalization and dissemination over the web, efficient sharing of ice data and information remains unsolved. Further, little has been done on analyzing specific sea ice data user requirements and developing flexible web-based processing and analytical services based on existing studies, which are useful for both sea ice and non-sea-ice data users. In this paper, we aim to develop a series of Google Maps-like sea ice web application programming interfaces (API) for JavaScript, which provide a flexible and easy-to-use way to enable online sea ice data sharing, visualization and spatio-temporal analyses. We identify sea ice data user requirements at different levels through investigating a group of interested Canadian northerners, and then we design and implement an online sea ice web APIs prototype. We also provide a web tool for registering and sharing other ice web services and an online web coding and debugging sandbox to facilitate and attract more sea ice users and developers. We believe this work will be a good example and potentially benefit the development of web APIs for sea ice data and information services as well as other relevant studies.